Multiple abiotic and biotic pathways shape biomass demographic processes in temperate forests. Issue 5 (8th April 2019) - Yuan, Zuoqiang; Ali, Arshad; Jucker, Tommaso; Ruiz‐Benito, Paloma; Wang, Shaopeng; Jiang, Lin; Wang, Xugao; Lin, Fei; Ye, Ji; Hao, Zhanqing; Loreau, Michel
Abstract: Forests play a key role in regulating the global carbon cycle, and yet the abiotic and biotic conditions that drive the demographic processes that underpin forest carbon dynamics remain poorly understood in natural ecosystems. To address this knowledge gap, we used repeat forest inventory data from 92, 285 trees across four large permanent plots (4–25 ha in size) in temperate mixed forests in northeast China to ask the following questions: (1) How do soil conditions and stand age drive biomass demographic processes? (2) How do vegetation quality (i.e., functional trait diversity and composition) and quantity (i.e., initial biomass stocks) influence biomass demographic processes independently from soil conditions and stand age? (3) What is the relative contribution of growth, recruitment, and mortality to net biomass change? Using structural equation modeling, we showed that all three demographic processes were jointly constrained by multiple abiotic and biotic factors and that mortality was the strongest determinant on net biomass change over time. Growth and mortality, as well as functional trait diversity and the community‐weighted mean of specific leaf area (CWMSLA ), declined with stand age. By contrast, high soil phosphorous concentrations were associated with greater functional diversity and faster dynamics (i.e., high growth and mortality rates), but associated with lower CWMSLA and initial biomass stock. More functionally diverse communities also had higher recruitment rates, but did not exhibit faster growth and mortality. Instead, initial biomass stocks and CWMSLA were stronger predictors of biomass growth and mortality, respectively. By integrating the full spectrum of abiotic and biotic drivers of forest biomass dynamics, our study provides critical system‐level insights needed to predict the possible consequences of regional changes in forest diversity, composition, structure and function in the context of global change.